2008
DOI: 10.3892/mmr_00000019
|View full text |Cite
|
Sign up to set email alerts
|

Long-lasting dephosphorylation of connexin 43 in acute seizures is regulated by NMDA receptors in the rat cerebral cortex

Abstract: Abstract. Gap junctions consisting of connexin 43 subunits provide intercellular communication between astrocytes, contributing to their function of maintaining the central nervous system (CNS) microenvironment. Magnetic resonance imaging (MRI) studies demonstrate prolonged astrocyte swelling related to seizures, while in vitro studies show the disruption of intercellular coupling and the cytotoxic swelling of astrocytes in seizure-equivalent environments. We examined the relation between astrocyte swelling an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
3
7
0
Order By: Relevance
“…NOX-induced oxidative stress transiently inhibits Na/K-ATPase, 36 restricting the uptake of extracellular K + (increased by several mM at the very beginning of seizure initiation 19 ) as well as the efflux of intracellular Na + , thus giving rise to focal network depolarization. In addition, we observed significant tissue (astrocytic) swelling coincident at seizure onset with the sentinel spike (see Fig 8A; see also Zador et al 38 ) that can augment the extracellular K + /glutamate concentrations even further by reducing extracellular volume. In addition, we observed significant tissue (astrocytic) swelling coincident at seizure onset with the sentinel spike (see Fig 8A; see also Zador et al 38 ) that can augment the extracellular K + /glutamate concentrations even further by reducing extracellular volume.…”
Section: Discussionsupporting
confidence: 60%
“…NOX-induced oxidative stress transiently inhibits Na/K-ATPase, 36 restricting the uptake of extracellular K + (increased by several mM at the very beginning of seizure initiation 19 ) as well as the efflux of intracellular Na + , thus giving rise to focal network depolarization. In addition, we observed significant tissue (astrocytic) swelling coincident at seizure onset with the sentinel spike (see Fig 8A; see also Zador et al 38 ) that can augment the extracellular K + /glutamate concentrations even further by reducing extracellular volume. In addition, we observed significant tissue (astrocytic) swelling coincident at seizure onset with the sentinel spike (see Fig 8A; see also Zador et al 38 ) that can augment the extracellular K + /glutamate concentrations even further by reducing extracellular volume.…”
Section: Discussionsupporting
confidence: 60%
“…Similar to Cx43, PKCε is also located in the mitochondria, which suggests a possible interaction between Cx43 and PKCε in the mitochondria (18). Increasing evidence indicates that the phosphorylation status of Cx43 is not static, but fluctuates in response to cell stress (19)(20)(21)(22). In the present study, decreased protein expression of PKCε was observed in the myocardial and mitochondrial protein extracts of the DCM rats, and the PKCε activities also decreased by ~60%.…”
Section: Discussionsupporting
confidence: 51%
“…Chronic unpredictable stressFa preclinical model that induces depressive-like symptoms in animalsFhas been shown to induce astrocytic gap junction dysfunction and consequent decreases in connexin 43, an astrocytespecific gap junction protein, in the PFC of rats (Sun et al, 2012). The effects of these manipulations have been shown both in vitro and in vivo to be glutamate dependent (Ozog et al, 2002;Zador et al, 2008). These results suggest that depressive-like outcomes correlate with increases in glutamate and astrocyte dysregulation that may lead to increases in glutamate-changes that, therefore, probably contribute to an anhedonic phenotype.…”
Section: Discussionmentioning
confidence: 99%